Kerja Sama Interpol – Britania Raya dalam Memerangi Kejahatan Siber: Studi Kasus Peningkatan Online Child Sexual Abuse di Britania Raya - Adinda Indah Karina; Reni Windiani; Shary Charlotte Pattypelohy (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Online Child Sexual Abuse is an Interpol’s term to define cybercrime in the form of sexual offenses against children. Creating a website domain containing graphic content or real images such as explicit sexual behavior and distribute some images of the child's sexual organs for sexual purposes and, or for other personal interest. This research aim to obtain an overview of online child sexual abuse, to get an overview of online child sexual abuse in the world in Europe, particularly in the United Kingdom from 2011 to 2015, and to know how Interpol efforts in dealing with cybercrime : online child sexual abuse and its effects against cases in the UK from 2011 to 2015, as well as knowing the obstacles in implementation of cooperation between Interpol with the United Kingdom that led to an increase in cases of OCSA each year. This research method is a qualitative descriptive research where the results are obtained from the primary data that is from interviews with relevant sources and secondary data from literature review by author’s analyst. There are two variables that will be analyzed by the author which are Interpol and United Kingdom. The results of this study is there are several obstacles from both parties. The constraint lies in the implementation of the regime by the United Kingdom which is the impact of the complexity of the international regime, that complexities are overlap regimes and parallel regimes.